2020
DOI: 10.13057/biodiv/d211259
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of lemon basil (Ocimum × africanum Lour.) from Indonesian archipelago based on morphological and inter-simple sequence repeats markers

Abstract: Abstract. Makmur K, Chikmawati T, Sobir. 2020. Genetic variability of lemon basil (Ocimum × africanum Lour.) from Indonesia based on morphological characters and ISSR markers. Biodiversitas 21: 5948-5953. Lemon basil (Ocimum × africanum Lour.) or kemangi is a highly beneficial plant, yet still underutilized. Therefore, providing necessary information on genetic diversity of this species is essential for further utilization. The aim of this study was to elucidate genetic diversity of 33 accessions of O. × afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Ten accessions of C. nucifera observed in each area showed similar characteristics to the population. This research is in line with (Makmur et al, 2020) who identified 27 accessions of basil (Ocimum x africanum Lour.). All of the observed O. x africanum accessions came from several regions in Indonesia.…”
Section: Resultssupporting
confidence: 89%
“…Ten accessions of C. nucifera observed in each area showed similar characteristics to the population. This research is in line with (Makmur et al, 2020) who identified 27 accessions of basil (Ocimum x africanum Lour.). All of the observed O. x africanum accessions came from several regions in Indonesia.…”
Section: Resultssupporting
confidence: 89%